Financing coastal land use planning: a case study of LUAS, Malaysia - Asmawi, M. Zainora; Md Din, Azrin (Elsevier, 2012)
Managing natural resources sustainably is essential in this contemporary era of town planning system. This includes managing and planning the invaluable of coastal areas. In this regards, coastal management programmes have been acknowledged as a primary approach in delivering the coastal strategies and objectives towards achieving a sustainable coastal development worldwide. As such, this paper suggests that town planning system as one key element of coastal management that can and should make a substantial contribution to planning and managing coastal land uses in Malaysia. Sustainable coastal management has many positive implications to the environmental, social and economic sectors. In addition, financial element has become a significant attribute in implementing coastal management initiatives successfully. This study offers input in planning literatures by addressing the integration of coastal management, town planning and financial elements which are very relevant with today’s current global changes on environment as a whole.